Organization Readiness and ERP Implementation in Albaha University - K Alaqeel; M S Shakkah; R F Rahmat; A Alfageeh; R Budiarto (IAES Indonesia Section, 2016)
This work studies the correlation between the organizational readiness in Albaha University and the respective Critical Success Factors with regards to the Enterprise Resource Planning (ERP) implementation. The study also considers some suggestions to improve the ABU’s ERP systems and roadmap towards the self –development strategy and to reduce vendor-dependency. A survey regarding ERP to the end-users, experts and developers in Albaha University was conducted. The analysis of the results in this work confirmed with the results of an existing work. The four significance success factors: Project Management, Business Process Re-engineering, System Integration, and Training and Education are recommended to be adopted to assure the smooth adoption of ERP at Albaha University.